Shipping Safety in the Singapore Strait Tanjung Pinang, Riau Islands, Indonesia - Siti Maemunah; Jerry Indrayanto Baka; Denny Najoan; Aswanti Setyawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
The purpose of this study was to determine the effectiveness of shipping safety in the Singapore Strait Shipping Channel, which is the Working Area of the Class I Navigation District of Tanjung Pinang, Riau Islands, Indonesia. With the increasing number of ships passing through the Singapore Strait, thus requiring Sailing-Navigation Assistance Facilities which are in line with the development of management and technology of Sailing-Navigation Assistance Facilities. The research method uses qualitative descriptive evaluation research methods and formal legality analysis, namely conducting an evaluation in the Singapore Strait in the Working Area of the Class I Navigation District of Tanjung Pinang. Observations by conducting observations in the waters of the Malacca Strait, interviews with Regulators, Operators and Service Users as well as conducting Focus Group Discussions and documentation related to shipping safety. From the three data sources, the findings of the e-Navigation study explain that it is effective to improve shipping safety in the Singapore Strait by implementing Virtual AIS AtoN. Regulations of a technical nature are indispensable for the implementation of e-Navigation in improving shipping safety